A Chiral Pool and Cross Metathesis Based Synthesis of Gingerdiols. Issue 10 (29th January 2014) - Wan, Zhi‐Li; Zhang, Guo‐Liang; Chen, Hui‐Jun; Wu, Yikang; Li, Yan
Abstract: Both (3 R, 5 S )‐ and (3 R, 5 R )‐gingerdiols were synthesized. Their 1, 3‐diol motifs were derived from enantiopure epoxy chiral building blocks that were readily accessible fromD ‐gluconolactone. The effect of deuterating the OH groups of the natural isomer on its optical rotation was also examined. In the course of the syntheses of the targets, an unexplored cross‐metathesis (CM) reaction of unprotected 5‐substituted pent‐1‐ene‐3, 5‐diols was investigated, in which the CM product readily underwent an allylic epimerization and oxidation, as the starting diols rearranged into ketones with unprecedented ease. These problems were eventually resolved by performing the CM reaction in toluene in the presence of phenol. The cause of these unexpected, yet very interesting phenomena, was determined to be the presence of the unprotected OH group at C‐5 of the 5‐substituted pent‐1‐ene‐3, 5‐diol. A mechanistic rationale is also presented. Abstract : During syntheses of the gingerdiols, a cross‐metathesis (CM) reaction that used unprotected 5‐substituted pent‐1‐ene‐3, 5‐diols was exploited. The expected CM product was accompanied by those resulting from an allylic epimerization and oxidation reaction, and a rearrangement of the starting diol into a ketone also took place. These problems were resolved, and a mechanistic rationale is presented.